1995
DOI: 10.1007/bf01781198
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the circulating cell adhesion molecule E-selectin and disease progression in HIV infection

Abstract: The levels of soluble form of E-Selectin (sEs), or endothelial-leukocyte adhesion molecule-1, were measured in 96 sera derived from 72 HIV-infected patients at different stages of the disease, 60 healthy blood donors, and 50 HIV-negative patients with infections, using a quantitative ELISA. Levels of sEs in HIV-infected individuals without AIDS, according to the 1993 classification system of the Centers for Disease Control, were higher than normal (mean +/- SEM 48 +/- 4 versus 35 +/- 3 ng/ml, p = 0.003). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…Although the immunological correlates of the elevated serum sCD40L levels associated with HIV-1 infection will require further study, we conclude that this molecule, unlike other non-T-cell-specific soluble molecules, which reflect panimmune system activation (15,16), could serve as an additional surrogate marker for the assessment of treatment efficacy. Such measurements could be useful in settings where wellequipped laboratories and funding required for CD4 ϩ T-cell and viral-load measurements are not available.…”
Section: Discussionmentioning
confidence: 86%
“…Although the immunological correlates of the elevated serum sCD40L levels associated with HIV-1 infection will require further study, we conclude that this molecule, unlike other non-T-cell-specific soluble molecules, which reflect panimmune system activation (15,16), could serve as an additional surrogate marker for the assessment of treatment efficacy. Such measurements could be useful in settings where wellequipped laboratories and funding required for CD4 ϩ T-cell and viral-load measurements are not available.…”
Section: Discussionmentioning
confidence: 86%
“…sEs is biologically active; it can inhibit leukocyte adhesion (29) and activate polymorphonuclear cells via the CD11b integrin receptor (44). As we have shown, levels of sEs in HIV-infected patients (without concomitant fever, opportunistic infection, or neoplasm) are elevated compared to those in healthy controls, while a significant increase was observed with disease progression (75). Although some subsequent studies confirmed the elevated levels of sEs compared to those for healthy controls (52,73), in other studies no significant differences were demonstrated (3,28,45) (Table 2).…”
Section: Soluble Selectins In Hiv Infectionmentioning
confidence: 80%
“…Individual serum sEs levels correlated strongly with levels of sICAM-1 and IL-2 receptor in serum but not with CD4 ϩ T-cell counts (75). Subsequent studies reported a marginal correlation or no correlation of sEs with CD4 ϩ T-cell counts (45,52).…”
Section: Prognostic Value Of Cams In Hiv Infectionmentioning
confidence: 94%
See 1 more Smart Citation
“…39 Other studies showed higher VCAM-1 and E-selectin levels in adult HIV patients with and without treatment, 40,41 and they were a potential marker of disease progression and death. 42,43 Recently, VCAM-1 was found to be associated with greater carotid intima media thickness in another study from our group. 44 Our current study is the first study showing the association of VCAM-1 and Eselectin with albuminuria in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 61%